2014
DOI: 10.1111/1469-0691.12645
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of pro-adrenomedullin, procalcitonin and C-reactive protein in predicting outcome of febrile urinary tract infection

Abstract: Bacterial infections such as febrile urinary tract infection (fUTI) may run a complicated course that is difficult to foretell on clinical evaluation only. Because the conventional biomarkers erythrocyte sedimentation rate (ESR), leucocyte count, C-reactive protein (CRP) and procalcitonin (PCT) have a limited role in the prediction of a complicated course of disease, a new biomarker-plasma midregional pro-adrenomedullin (MR-proADM)-was evaluated in patients with f UTI. We conducted a prospective multicentre co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 30 publications
4
20
0
13
Order By: Relevance
“…Also, other studies have shown that ESR and leucocyte count don't have a great value in predicting outcome of febrile UTI (10,11). The results of our study and similar studies demonstrate that ESR changes relatively slowly as the patient's condition improves (12).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Also, other studies have shown that ESR and leucocyte count don't have a great value in predicting outcome of febrile UTI (10,11). The results of our study and similar studies demonstrate that ESR changes relatively slowly as the patient's condition improves (12).…”
Section: Discussionsupporting
confidence: 67%
“…Although serial measurement of ESR level has been advocated for monitoring of disease processes in adulthood infections, most recent studies tend to favor pro-adrenomedullin, procalcitonin, and C-reactive protein over ESR, mainly because of the fact that ESR is affected by a multitude of factors (10).…”
Section: Discussionmentioning
confidence: 99%
“…Half of ureter stones recur within 5 years. A low CRP might exclude other infectious conditions, such as acute pyelonephritis or renal abscess [22]. C-reactive protein could also be used as a predictor of spontaneous passage of ureter stones.…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of primary care, in smaller studies ProADM was associated with mortality in patients with urinary tract infections [43], type 2 diabetes [4345] or heart failure [25, 4649]. It is not known whether this marker helps to predict long-term risk, which could be useful for directing preventive measures.…”
Section: Introductionmentioning
confidence: 99%